The Role of L-Arginine/Nitric Oxide Pathway in the Antinociceptive Activity of Pyridoxine in Mouse - Abacioğlu, Nurettin; Tunçtan, Bahar; Çakici, İiclal; Akbulut, Esen; Uludağ, Orhan; Kanzik, İlker (Arzneimittelforschung, 2001)
In the present study the role of L-arginine/nitric oxide (NO)/cGMP pathway in the antinociceptive activity of pyridoxine in p-benzoqulnone-lnduced abdominal constriction test in mouse was investigated. Pyridoxine (CAS 58-56-0) displayed dose-dependent antinociceptive activity at 0.0625-1 mg/kg (s.c.), doses. L-arginine (CAS 1119-34-2), a NO precursor, displayed a triphasic pattern as antinociception-noclception- antinoclception (61.8 ± 7.8, -36.5 ± 12.7 and 17.0 ± 4.3 %, 5, 40 and 50 mg/kg, s.c, respectively). The antinociceptive effect of pyridoxine at ED50 dose (0.43 mg/ kg, s.c.), (47.7 ± 3.9 %) was significantly decreased by L-arginine at 40 and 50 mg/ kg doses (4.1 ± 9.3 and 37.8 ± 1.6 %, respectively) while 5 mg/kg dose of L-arginine significantly potentiated the pyridoxine analgesia. On the other hand, pyridoxine reversed the L-arginine-lnduced nociception to anti-noclception(4.1 ± 9.3 %) and augmented the antinociceptive effect of L-arginine (37.8 ± 1.6 %). L-NG-nitroarginine methyl ester (CAS 51298-62-5), a NO synthase Inhibitor, at 75 mg/kg, s.c. produced antinociception and significantly increased the antinociceptive effect of pyridoxine (63.7 ± 1.2 %). Methylene blue (CAS 61-73-4, MB), a guanylyl.cyclase and/or NO synthase inhibitor, was antinociceptive and nociceptive at 5 and 40 mg/kg doses, respectively. 5 mg/kg dose of MB significantly increased the antinociceptive effect of pyridoxine, but did not change it at 40 mg/kg dose. On the other hand, pyridoxine significantly decreased the antinociceptive effect of MB and reversed the MB-induced nociception to antinociceptlon. Combination of pyridoxine and morphine (CAS 57-27-2) (ED50: 0.13 mg/kg, s.c.) at 49.8 ± 1.9 % revealed a significant antinociceptive potentiation (69.1 ±1.8 %). The findings of the present study emphasise the contribution of central and/or peripheral L-arginine/NO/ cGMP nociceptive processes in pyridoxine-induced antinoclception.
Keywords: L-Arginine/NO/cGMP, role in antinociception; CAS 58-56-0; CAS 1119-34-2; Pyridoxine, antinociceptive effect, mouse